Substituent effects on the electrocatalytic activity of cobalt phthalocyanine in the presence of graphene quantum dots - Centane, Sixolile Sibongiseni (Rhodes University, Faculty of Science, Department of Chemistry, 2019)
The electrocatalytic activity of metallophthalocyanines derivatives is explored. Cobalt monocarboxyphenoxy phthalocyanine (1), cobalt tetracarboxyphenoxy phthalocyanine (2), cobalt tetraaminophenoxy phthalocyanine (3) and cobalt tris-(tert-butylphenoxy) monocarboxyphenoxy phthalocyanine (4) are the phthalocyanines employed in this work. The metallophthalocyanines were employed alone as well as in the presence of the carbon based graphene quantum dots. The electrocatalytic behaviour of functionalized GQDs is also explored herein. The catalytic processes studies were conducted on a glassy carbon electrode surface. Modification of the electrode was achieved by the adsorption method. The materials were adsorbed either alone, as premixed/covalently linked GQDs/Pc conjugates or sequentially. Sequentially adsorbed electrodes involved the phthalocyanines on top or beneath GQDs. Sequentially modified electrodes where the phthalocyanine had higher currents and low detection limits than when the phthalocyanine is underneath. Premixed conjugates showed better activity than the covalently formed conjugates. The nanomaterials synthesized and used in this work were characterized using transmission electron microscopy, UV-Vis spectroscopy, dynamic light scattering, Raman spectroscopy, X-ray diffraction, Atomic Force Microscopy and X-ray photoelectron spectroscopy. The modified electrodes were characterized using cyclic voltammetry and scanning electrochemical spectroscopy. The electrocatalytic activity of the modified electrodes towards the oxidation of hydrazine was evaluated using cyclic voltammetry and chronoamperometry. Superior catalytic activity was observed for the conjugates compared to that of the individual conjugates.
Keywords: Phthalocyanines; Quantum dots; Electrocatalysis; Electrochemistry